Teak furniture and business responsibility: a global value chain dynamics approach - Purnomo, H. (2006)
Teak furniture business development aims at achieving the three millenium development goals of global partnership, poverty alleviation and environmental sustainability. A value chain of teak furniture connects teak growers with furniture retailers in Europe, the United States and Japan. It distributes value added along the chain, but it produces imbalance of income distribution and pressure on teak plantation sustainability. This paper integrates value chain analysis and system dynamic approach to observe and system dynamic approach to observe baseline trends and glimpse future scenarios of teak forest and incomes to various actors participating in the teak business. Future scenarios to obtain premium prices through fair trade and business responsibility of international furniture retailers will not only restore the teak furniture business but also foster great leap in teak plantation sustainability and livelihoods of teak growers and small to medium-sized teak furniture enterprises. Collective action among them in defining rules and a low level of land conflicts are necessary conditions for success.